Impact of heavy smoking on the benefits from first-line EGFR-TKI therapy in patients with advanced lung adenocarcinoma. Issue 9 (March 2018) - Zhang, Ping; Nie, Xin; Bie, Zhixin; Li, Lin
Abstract : Abstract: Smoking is a risk factor for nonsmall cell lung carcinoma (NSCLC) and is associated with a lower response to epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKI). The purpose of this study is to examine the impact of the smoking status on the benefits from first-line EGFR-TKI in NSCLC patients with EGFR mutation. This was a retrospective study of 159 patients with advanced NSCLC treated at the Beijing Hospital between January 2011 and December 2016. The follow-up was censored on December 2017. EGFR mutation status, smoking (nonsmoker vs <30 packs/year (light smoker) vs ≥30 packs/year (heavy smoker)), treatment, treatment response, and progression-free survival (PFS) were collected from the charts. Median follow-up was 10.0 (1.0–36.6) months. Response rate was lower in heavy smokers compared with nonheavy smokers (19.0% vs 71.7%, P  < .001). There was no difference in PFS between nonsmokers (median, 10.5 months) and light smoker (median, 11.0 months), and these 2 groups were pooled together. PFS was longer in nonheavy smokers compared with heavy-smokers (median, 10.7 vs 6.0 months, P  < .001). Smoking ≥ 30 packs/year (HR = 2.48, 95% CI: 1.55–3.98, P  < .001) was associated with PFS. In patients with advanced NSCLC, the benefits and PFS of EGFR-TKI were better for nonheavy smokers than for heavy smokers.